Insertional mutagenesis identifies a member of the Wnt gene family as a candidate oncogene in the mammary epithelium of int-2/Fgf-3 transgenic mice. - Lee, F S (1995)
Transgenic mice harboring the int-2/Fgf-3 protooncogene under transcriptional control of the mouse mammary tumor virus (MMTV) promoter/enhancer exhibit a dramatic, benign hyperplasia of the mammary gland. In one int-2 transgenic line (TG.NX), this growth disturbance is evoked by pregnancy and regresses after parturition. Regression of hyperplastic mammary epithelium is less complete after successive pregnancies, and, within 10 months, most TG.NX mice stochastically develop mammary carcinomas that are transplantable in virgin, syngeneic mice. To identify genes that cooperate with int-2 in cell transformation, we infected TG.NX transgenic mice with MMTV. In a cohort of 14 animals, most mammary tumors represented clonal or oligoclonal outgrowths harboring one to five proviral MMTV integrants. Eight of 35 (23%) MMTV+ tumors exhibited proviral insertion at the Wnt-1 locus. No provirus was detected at the int-2, int-3, or Wnt-3 loci. By Southern analysis, two tumors had proviral insertions at the same genomic location, which was mapped to chromosome 15. Cloning of this int locus identified an additional member of the Wnt gene family. The predicted 389-amino acid protein is most closely related to zebrafish Wnt-10a (58% amino acid identity over 362 residues) and, based on homology analysis, was designated Wnt-10b. This newly discovered Wnt family member was expressed in the embryo and mammary gland of virgin but not pregnant mice and represents a candidate collaborating oncogene of int-2/Fgf-3 in the mammary epithelium.